2017
DOI: 10.1002/art.40164
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Soluble Forms of Programmed Death 1 and Programmed Death Ligand 2 to Disease Severity and Progression in Systemic Sclerosis

Abstract: These results suggest that sPD-1 and sPD-L2 contribute to disease development in SSc via the regulation of cognate interactions with T cells and B cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 44 publications
5
58
1
Order By: Relevance
“…1C). In addition, serum levels of soluble forms of PD-1 and its ligand PD-L2 were recently shown to be elevated in SSc (14). Li et al describe increased TIM-3 on CD4 + and CD8 + T cells in peripheral blood from rheumatoid arthritis patients (39), while our data show no changes in TIM-3 in SSc T cell subsets, but an increase in NK cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1C). In addition, serum levels of soluble forms of PD-1 and its ligand PD-L2 were recently shown to be elevated in SSc (14). Li et al describe increased TIM-3 on CD4 + and CD8 + T cells in peripheral blood from rheumatoid arthritis patients (39), while our data show no changes in TIM-3 in SSc T cell subsets, but an increase in NK cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, an exhaustion-like phenotype marked by an increase in co-IR expression correlated with less flares in lupus patients (10), while the presence of TIM-3 + T cells was associated with milder forms of multiple sclerosis (13). In SSc, a recent report indicates that the PD-1 pathway is involved in regulating disease severity (14). …”
Section: Introductionmentioning
confidence: 99%
“…Programmed death‐1 (PD‐1) is a molecule expressed on various human immune cells, including T cells, B cells, myeloid cells, thymocytes and natural killer (NK) cells . The ligation of programmed death ligand‐1 (PD‐L1) and programmed death ligand‐2 (PD‐L2) to PD‐1 may have an inhibitory effect on target cells (eg T cells), playing an important role in the regulation of immune homeostasis and in maintenance of peripheral immune tolerance . PD‐1 expression correlates with the exhaustion of T cells in cancers and chronic infections .…”
Section: Introductionmentioning
confidence: 99%
“…Even in this study, highly elevated serum IL‐6 levels were observed in active SSc‐ILD. In our previous study using mice where an immune response was elicited using a topoisomerase I protein, activation of T and B cells and macrophages and induction of lung fibrosis were observed . By contrast, the immune cell activation and fibrosis were significantly suppressed in IL‐6R knockout mice.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, we have successfully integrated the immunoassay into a microchip, applying basic enzyme‐linked immunoassay (ELISA) methodology to the micro‐ELISA system . This system can measure the very low concentration (10–1000 fg/mL) of several cytokines using a bead‐bed immunoassay on a microchip composed of flow channels that are 5–100 μm in depth.…”
Section: Case Reportmentioning
confidence: 99%